Answer:
( No)
Step-by-step equation:
System of Linear Equations entered :
[1] y=-4+6
[2] 3x+4y=-2
Equations Simplified or Rearranged :
[1] y = 2
[2] 4y + 3x = -2
Graphic Representation of the Equations :
0? + y = 2 3? + 4y = -2
Solve by Substitution :
// Solve equation [1] for the variable y
[1] y = 2
// Plug this in for variable y in equation [2]
[2] 4•(2) + 3x = -2
[2] 3x = -10
// Solve equation [2] for the variable x
[2] 3x = - 10
[2] x = - 10/3
// By now we know this much :
y = 2
x = -10/3
We are done
Solution :
{y,x} = {2,-10/3}